Rethinking the Borders of Islamic art: Paterna ceramics from the fourteenth century to today - Mc Sweeney, Anna (Equinox Publishing Limited, 2022)
Recent scholarship in Islamic art and architecture has seen a growing interest in art from the borderlands – the borders of empires, peoples, religions and practices. In this context, the art of Muslim majority populations in post-Islamic Spain should be front and centre, but instead it has languished in the obscure and antiquated classifications of 'Hispano-Moresque' and 'mudéjar'. How then can we consider ceramics such as the glazed and decorated tableware made in 14th century Paterna by Muslim potters under Christian rule? Where does the material culture of these border communities fit in the politics of excavation, museum display and academic scholarship and do the porous borders of Islamicate art offer a solution? This paper will examine these questions through a detailed study of the production, distribution, excavation and re-discovery of Paterna ceramics.
Archaeology, Politics and Islamicate Cultural Heritage in Europe
Keywords: Islamic art; Archaeology; Ceramics; Spain; Art history; Islamicate; Islamic archaeology; Islamic art